Dampak Penggunaan Gadget pada Interaksi Sosial Anak Usia Dini - Nur Mutmainnatul Itsna; Risatur Rofi’ah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
Gadget is an electronic device that has a special function on each device. It is important to understand the influence of gadgets, especially for parents, so that parents can limit their children's use of gadgets so that children's developmental abilities develop well and become active, intelligent, and interactive children with others. Excessive use of gadgets will be able to affect the lack of social interaction in children in the environment. Based on the description above, the formulation of the problem in this study can be determined, namely (1) How is the impact of gadget use on early childhood social interaction in Sendangagung Paciran Lamongan Village (2) What are the factors that influence the use of gadgets in early childhood. The purpose of this study is to find out how the impact of using gadgets on early childhood social interactions in Sendangagung Paciran Lamongan Village and to find out what are the factors that influence the use of gadgets in early childhood. In this study, researchers used descriptive qualitative research methods. Data collection procedures are interviews, observation and documentation. Checking the validity of the data carried out is triangulation. The results of this study indicate that the use of gadgets in early childhood has positive and negative impacts. The positive impact is making it easier for a child to obtain information and making children more creative through the available features, while the negative impacts include lack of interaction, decreased social skills, dependence. by gadgets. From these results, it is suggested that future researchers can develop other variables so that they will enrich scientific findings in the impact of gadget use on early childhood.